Địa lí các tỉnh và thành phố Việt Nam - Lê, Thông (Giáo Dục, 2003)
Giới thiệu địa lí của các địa danh như Hà Nội, Bắc Ninh, Hà Nam, Hà Tây, Hải Dương, Hải Phòng, Hưng Yên, Nam Định, Ninh Bình, Thái Bình, Vĩnh Phúc.